Information Literacy Instructions in Higher Education Institutions: Enhancing Academic Success and Research Competencies among University Students in the United Arab Emirates - Khan, Zafar Imam; Sohail , Md. (DESIDOC Journal of Library & Information Technology, 2025)
The study explores the impact of Information Literacy (IL) programs on undergraduate students on their learning outcomes and performance in terms of research skills required for academic writing. The study also investigates the significant differences of learning outcomes in terms of gender, year of program and EFL/Non-EFL learners. Through systematic quantitative analysis involving 102 participants using stratified random sampling across multiple universities in the United Arab Emirates, this study seeks to validate assumptions regarding the correlation between information literacy and its significance in academic and research achievement. Findings revealed that there was moderate to higher level improvement in students’ critical thinking and overall research skills, with notable advances observed in academic integrity awareness, database searching techniques and source evaluations, whereas citation practices and advanced search strategies need more improvement. Some correlations were also found between IL program usefulness and improvement in academic performance, time utilisation and citation skills. The key findings of this study will underscore the transformative potential of information literacy programs and highlight the need to customize them as per the requirements in academic libraries as learning centers and their essential role in fostering student competencies that correspond with educational and professional success. Recommendations include targeted intervention, curriculum-integrated IL workshops and adoption of citation management tools.